Nanostructured Transparent Electrodes: A Self‐Ordered Nanostructured Transparent Electrode of High Structural Quality and Corresponding Functional Performance (Small 20/2021). Issue 20 (20th May 2021) - Döhler, Dirk; Triana, Andrés; Büttner, Pascal; Scheler, Florian; Goerlitzer, Eric S.A.; Harrer, Johannes; Vasileva, Anna; Metwalli, Ezzeldin; Gruber, Wolfgang; Unruh, Tobias; Manshina, Alina; Vogel, Nicolas; et al.
Abstract : In article number 2100487, Ignacio Mínguez‐Bacho and co‐workers report the fabrication of highly ordered nanoporous transparent electrodes using nanosphere lithography and anodization. The self‐assembly methods used result in perfect hexagonal order over domains of thousands of square micrometers. Solar cells made from them reach significantly improved performance compared to their disordered counterparts.